The cyber threat from Pyongyang - Nah, Liang Tuang (2023)
Poverty-stricken North Korea spends a lot of its national resources on the military, including cyber, capabilities. Its cyber units, especially Bureau 121, are assumed to possess sophisticated cyber espionage capabilities, operating systems, and intrusion software; and the expertise to create highly destructive malware deliverable online to networked computers, or to standalone systems autonomous of the internet. Military and national security planners must implement relevant threat mitigation measures in the face of Pyongyang’s cyber offensives.